Meningkatkan Pembelajaran Melalui Teknologi Digital - Abdul Sakti (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Learning through digital technology has changed the traditional learning paradigm by providing new opportunities for students to develop skills and knowledge. Through interactive learning methods, diverse media, and the flexibility of distance learning, digital technology enables students to be actively involved in the learning process. Students can access information-rich digital resources, ranging from e-books to learning videos, which help increase absorption and understanding of material. In addition, collaboration and interaction between students is also enhanced through online learning platforms, enabling them to share ideas, support one another, and learn together in a virtual environment. Digital technology also helps students develop skills relevant to the digital era, such as digital literacy, critical thinking, and the ability to adapt to changes in technology. In this era, it is important for educators and educational institutions to continue to integrate digital technology with appropriate learning strategies, so that students can take advantage of the potential of this technology to improve their learning.